Relational Model of Organizational Politics Perception, Job Satisfaction, Job Stress, and Organizational Commitment in Hospital Nursing Staff - Su-Yueh Chen; Jaw-Yuan Wang; Ching-Sheng Chang; Hui-Ching Weng (Archives of Nursing Practice and Care - Peertechz Publications, 2017)
Objectives: This study investigated the correlations between the organizational politics perception, job satisfaction, job stress, and organizational commitment of the hospital employees in a medical centre. This will allow managers at various levels to understand better the organizational politic perception of the hospital nursing staff, which will enable them to reduce the negative impacts of hospital nursing staff's organizational politics perception and job stress, and improve the job satisfaction and organizational commitment of hospital employees. Accordingly, the hospital will become more competitive and achieve sustainable operation. Methods: We adopted a cross-sectional design using a questionnaire survey. In this study, the convenience sampling method was applied to the nurses of the hospital. A total of fi ve hundred questionnaires were distributed between March 2017 and May 2017, and four hundred and fi fty seven ones were returned; 448 of the copies were valid, with a valid response rate of 89.6%. The SPSS 18.0 and Amos 18.0 (structural equation modeling) software were used for data analysis. Results: Hospital nursing staff's organizational politics perception has a signifi cant negative effect on their job satisfactionand organizational commitment. Hospital nursing staff's organizational politics perception has a signifi cant positive effect on their job stress. Hospital nursing staff's job satisfaction has a signifi cant positive effect on their organizational commitment. Hospital nursing staff's job stress has a signifi cant negative effect on their organizational commitment. Conclusion: This study recommends that hospitals establish good communication management mechanisms so that supervisors can effectively communicate with hospital nursing personnel and increase mutual reliance. This can reduce effects from political behaviour and not let hospital nursing personnel feel stressed because of political behaviour. Hospital nursing personnel should be appropriately encouraged to increase their work motivation and service spirit. These results indicate that to reduce hospital personnel work stress, hospital nursing management should pay attention to the function of each position and determine whether the workload of each hospital nurse is appropriate. Positive advice and encouragements for hospital nursing personnel must be given and guidance for inadequacies must be provided to allow hospital nursing personnel in the team to have the opportunities to learn and grow.